Analysis of Work Coordination, Work Environment and Infrastructure on Job Satisfaction of Nursing Officers in General Hospital dr. Moh. Anwar Sumenep District - Hermanto; Agusta Dian Ellina (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Job satisfaction is the general attitude of an individual towards the work he does. A person with a high level of job satisfaction shows a positive attitude towards what he does. The purpose of this study is to analyzethe effect of work coordination, work environment and infrastructure on job satisfaction of nursing officers in hospitals. dr. Moh. Anwar, Sumenep Regency. The design of this research is an observational quantitative research with a cross sectional approach with the focus of the research being directed at analyzingthe effect of work coordination, work environment and infrastructure on job satisfaction of nursing officers in hospitals. dr. Moh. Anwar, Sumenep Regency. The total population is 302 respondents and a sample of 172 respondents is taken by using Simple Random Sampling technique. The research shows that most of the respondents have good work coordination as many as 88 respondents (51%). Most of the respondents have a good working environment category as many as 91 respondents (53%). Almost half of the respondents have adequate infrastructure facilities as many as 73 respondents (42%). Most of the respondents have job satisfaction satisfied category as many as 113 respondents (66%). Based on the results of Multiple Linear Regression analysis shows that with a p- value of 0.000 < 0, 05 then H1 is accepted so it can be concluded that simultaneously there is an effect of work coordination, work environment and infrastructure on the job satisfaction of nursing officers in hospitals. dr. Moh. Anwar, Sumenep Regency with an influence of 82.7%. It is hoped that health workers can provide input to related agencies on everything that can increase job satisfaction, so that it can be mutually beneficial between patients, health workers and agency superiors and their staff.